An Improved Response of Multi Level Inverter Based PR Controlled SMPS - Sasikala, K.; Krishnakumar, R. (Frontiers in Energy Research, 2020)
This paper mainly focuses on identifying an optimum controller for a Multi Level Inverter Based Switched Mode Power Supply (MLIBSMPS) for constant voltage applications. Generally, there is a greater demand of constant voltage for sensitive loads. A closed-loop control is introduced in the circuit in order to obtain constant voltage quickly. In this paper, closed-loop Proportional Integral (PI) as well as Proportional Resonant (PR) controlled MLI based SMPS systems are simulated and the comparison of their performances are done. It is seen that acceptable performance is achieved using PR controlled MLI based SMPS than PI Controlled MLI based SMPS. It also proves that PR Controlled SMPS with 7 level inverters has reduced steady-state error and improved time-domain response as compared to PI Controlled SMPS.